PEMAHAMAN MASYARAKAT TENTANG PERBANKAN SYARIAH (STUDI KASUS DI DESABARU HINAI KABUPATEN LANGKAT) - Dewi Elvita Sari; Anjur Perkasa Alam; Diyan Yusri (EKSYA : Jurnal Ekonomi Syariah, 2022)
In terms of development, Islamic banks are currently not behind with progress like conventional banks. Conventional banking that implements the interest system goes hand in hand with Islamic banking that implements a profit-sharing system. The problem faced by Islamic banks is the low level of public knowledge about Islamic banking, especially due to the dominance of conventional banking so that Islamic banking is still considered one eye. The purpose of this study was to find out how the public's understanding of Islamic banking in Baru Hinai Village. This type of research is a field research (Field Research) conducted in the village of Baru Hinai. The nature of this research is a qualitative descriptive method. There are two sources of data in this study, namely primary data sources and secondary data sources. The primary data sources were obtained directly from the community while the secondary data sources that the researchers used were in the form of documents from the Baru Hinai Village and from various books. To obtain valid data, researchers used data collection methods, namely interviews. After the data was collected, the researchers analyzed using qualitative data analysis techniques using inductive methods. The results of research in the field show that the understanding of the community about Islamic banks in Baru Hinai Village is that people only know about Islamic banks but do not understand Islamic banks in detail. Only some people understand about Islamic banks and some even don't know anything about Islamic banks. Most people do not know what products and services are in Islamic banks. The lack of understanding from the public is due to the lack of information obtained from Islamic banks and media such as television, print media and social media which causes people not to know what Islamic banks are and what products are available in Islamic banks